2010
DOI: 10.1523/jneurosci.1044-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-A Stabilizes the Architecture of Hippocampal Neurons

Abstract: Although the role of myelin-derived Nogo-A as an inhibitor of axonal regeneration after CNS injury has been thoroughly described, its physiological function in the adult, uninjured CNS is less well known. We address this question in the hippocampus, where Nogo-A is expressed by neurons as well as oligodendrocytes. We used 21 d in vitro slice cultures of neonatal hippocampus where we applied different approaches to interfere with Nogo-A signaling and expression and analyze their effects on the dendritic and axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 64 publications
7
86
1
1
Order By: Relevance
“…During development, Nogo-A influences migration and neurite outgrowth of cortical neurons [31], conducts corticospinal axons growing along the spinal cord, and regulates the progressive restriction of plasticity [8,27]. Few data from studies on adult brains have been published suggesting that NogoA constitutively controls the architecture of neurons in the intact hippocampus (mainly via a receptor mediated mechanisms) [33,44]. Moreover, electrophysiological studies revealed that NogoA or NogoA receptor neutralisation significantly increased the long term potentiation in hippocampal neurons [7].…”
Section: Discussionmentioning
confidence: 99%
“…During development, Nogo-A influences migration and neurite outgrowth of cortical neurons [31], conducts corticospinal axons growing along the spinal cord, and regulates the progressive restriction of plasticity [8,27]. Few data from studies on adult brains have been published suggesting that NogoA constitutively controls the architecture of neurons in the intact hippocampus (mainly via a receptor mediated mechanisms) [33,44]. Moreover, electrophysiological studies revealed that NogoA or NogoA receptor neutralisation significantly increased the long term potentiation in hippocampal neurons [7].…”
Section: Discussionmentioning
confidence: 99%
“…9 In the adult CNS, Nogo-A proteins are located at synapse and restrict synaptic plasticity 10 and stabilize the architecture of hippocampal neurons. 11 To date, new findings of neuronal Nogo-A are logically in line with localization of Nogo-A and Nogo-66/NgRmediated signaling; however, concrete evidence for a direct role of amino-Nogo-A in the CNS is not yet available.…”
mentioning
confidence: 89%
“…It is noteworthy that NogoA/NgR1 are expressed in pyramidal cells of the hippocampus (12), that their expression is regulated by neuronal activity (16,17), and that NgR1 is located at synapses in the adult CNS (18). However, the physiological role of neuronal NogoA in the hippocampus of adult animals has remained largely unexplored (for a review see ref.…”
mentioning
confidence: 99%